EFEKTIVITAS BEBERAPA INSEKTISIDA NABATI TERHADAP HAMA Plutella xylostella Linn. (Lepidoptera; Plutellidae) PADA TANAMAN KUBIS (Brassica oleracea L.) DI KABUPATEN MINAHASA - Margaretha S. Ginting; Jantje ., Pelealu; Betsy A. N. Pinaria (Sam Ratulangi University, 2017)
This study aims to: (1) Know the effectiveness of plant insecticides plant extracts Tiger Grass, Nutmeg Seeds and Bitung Fruits against cabbage caterpillar Plutella xylostella L. on cabbage plants? (2) Analyzed the mortality of the cabbage of Plutella xylostella L. cabbage on cabbage plants in Minahasa Regency on the administration of plant insecticide plant extracts of Nutmeg, Tiger Grass and Bitung Fruit.Â This research was conducted from July to November 2017 using a Completely Randomized Design (RAL), consisting of 4 treatments and 3 replicates. Field sampling of cabbage plants was conducted on 12 sub-plots. Every 7 days the number of P. xylostella larvae is observed. Observations were performed before spraying, and 1 day after spraying, as well as on week II to week V observations, for the collection of P. xylostella pupa done on 1 day after spraying, the number of pupa collected per sub-plot was 5 pupa so that 15 pupa collected, the total number of pupa 60 pupa. Then the pupa collected was placed in the prepared container and then observed the development. The results showed that: (1) The test result from Seed Nut extract, Tiger Grass extract and Bitung Fruit at concentration of 15% to mortality of Plutella xylostella larvae showed the significant difference of each treatment with the highest mortality rate of Plutella xylostella larvae 87,07% on Fruit extract treatment Bitung, Tiger Grass extract 78.09 percent, on Seed Nut extract 74.44 percent and 22.55 percent on control. (2) The test result from Seed Extract of Nutmeg, Bitung and Tiger Grass on the mortality of Plutella xylostella larvae showed significant difference of each treatment with higher concentration of extract treatment, the higher the mortality of Plutella xylostella larvae.Â